Viral Regulation on Bacterial Community Impacted by Lysis-Lysogeny Switch: A Microcosm Experiment in Eutrophic Coastal Waters - Chen, Xiaowei; Ma, Ruijie; Yang, Yunlan; Jiao, Nianzhi; Zhang, Rui (Frontiers in Microbiology, 2019)
Marine viruses are major drivers of global biogeochemical cycles and energy fluxes, yet the importance of viral impacts on the succession and diversity of the bacterial community remains largely unexplored. Here, we explored viral life strategy and its potential effect on the bacterial community by experimental incubations of eutrophic coastal waters under lysogen-induced and non-induced treatments. The lysogen-induced treatment showed relatively constant viral and bacterial abundances, lytic and lysogenic viral production throughout the experimental period, together with the progressive declines in not only the relative abundances for SAR11, Rhodobacteraceae, Altermonadaceae and SAR86 but the bacterial community diversity. Conversely, the non-induced treatment observed the marked variation in the abundances of viruses, bacteria and cells with high nucleic acid content over the time course of incubation, which was congruent with the drastic shift in lytic and lysogenic viral production as well as the succession of bacterial community. Our results supported the hypotheses that a high level of lysogeny would occur with the increasing density of bacteria with rapid growth rate, which may contribute to a relatively lower host community diversity, whereas the lysogeny to lysis switching would fuel growth opportunities for less-active or initially rare bacterial taxa and generate a more diverse bacterial community. Altogether, the present study underscored the crucial regulatory role of the viral lysis-lysogeny pattern in bacterial community dynamics, composition and diversity, highlighting the viral impact on the microbial food web and biogeochemical processes.